Analisis Perilaku Pencegahan Child Sexual Abuse Oleh Orang Tua Pada Anak Usia Sekolah - Nian Afrian Nuari (coba, 2016)
Child abuse is part of the kind of violence that is characterized by any properties of hurting or harassing of sexual. Child sexual abuse is not only a negative impact on the micro level only (individual and family), but it also could have an impact on the process of social development in the future will come. Preventive child sexual abuse in school age children is not optimal due to several factors. The aim of research to analyze factors associated with child abuse prevention behavior of school-age children (6-8 years). The research design is correlational design with cross sectional approach. The population is all mothers in SDN Kawedusan 1 Kediri much as 73 mothers with a sample of 22 respondents taken by purposive sampling technique. The result showed mostly maternal age 20-35 years old, high school educated, have jobs as the private sector, knowledge of early sexual education categories of good and positive maternal attitude towards the prevention of child sexual abuse in school-age children. Based on the analysis of Spearmean rho test obtained child sexual abuse prevention behaviors in school-age children have a correlation with the mother's age factor (p = 0.021), maternal education (p = 0.028), mother's occupation (p = 0.036), knowledge mothers about early sexual education (p = 0.002) and attitude of mothers in the prevention of child sexual abuse behavior (p = 0.001). Based on these results it is expected that the capital increase knowledge about sexual education early in order to carry out the role in sex education so that preventive measures implemented in the environment of child sexual abuse. Keywords: analysis, mother, behavior, child, sexual, abuse